Pembrolizumab plus Pemetrexed and Platinum in Metastatic Non-Squamous Non-Small Cell Lung Cancer: A Real-Life Study at a Portuguese Centre - Maria João Santos; Filipa Ferro; Andrea Machado; Ana Sofia Vilariça; Direndra Hasmucrai; Paula Alves (Acta Médica Portuguesa)
First-line therapy for metastatic non-small-cell lung cancer without targetable mutations is platinum-based chemotherapy plus pembrolizumab if programmed death ligand 1 is < 50%. The aim of this real-life retrospective study is to assess the efficacy and safety of this therapy. This retrospective observational study was conducted at the Pulmonary Oncology Department in Unidade Local de Saúde Santa Maria, in Lisbon, Portugal. We included patients with stage IV non-squamous non-small-cell lung cancer with programmed death ligand 1 < 50% that started pembrolizumab plus platinum and pemetrexed between July 2020 and December 2022. Follow-up was carried out until September 2023. Progression-free survival, overall survival, response rate and safety were evaluated. Sixty-six patients were included. Median age 67 years, 72.7% male, 92.4% performance status 0 - 1, 90.9% current/former smokers. Programmed death ligand 1 < 1% in 63.6%. Median overall and progression-free survival were 12.2 months and 6.7 months, respectively. At the time of the cut-off, 21.2% of patients were alive and progression-free. The objective response rate was 42.4% (partial response). The disease control rate was 69.7%. Adverse events occurred in 92.4%, 43.9% had grade 3 - 4 adverse effects. The most common were anemia (50.0%), neutropenia (40.9%), and asthenia (36.4%). Treatment was discontinued in three patients due to adverse effects. There were no treatment-related deaths reported. With median progression-free survival and overall survival of 6.7 and 12.2 months, respectively, and no new safety signals, these results complement data from clinical trials, providing information from a real-world setting.